Gender Differences in Psychosocial Predictors of Sexual Activity and HIV Testing Among Youth in Kenya - Chenneville, Tiffany; Drake, Hunter (Frontiers in Reproductive Health, 2021)
Sub-Saharan Africa (SSA) carries a disproportionate burden of HIV in the world relative to its population. Youth are at particular risk. Understanding HIV risk factors, as well as factors affecting HIV testing among SSA youth, is important given that HIV testing, linkage to care, and viral suppression are part of the global strategy to end HIV. Because young women face disparate sexual and reproductive health outcomes, exploring gender differences related to HIV risk, and testing is vital. Using existing program evaluation data from a larger project, the purpose of this study was to explore gender differences related to sexual activity and HIV testing among youth in SSA. Participant data from 581 youth ages 13–24 in Kenya was analyzed using descriptive statistics, analysis of covariance, and binomial logistic regression. Findings revealed that young men were more likely to report sexual activity than young women. Age was a predictor of sexual activity for all youth. However, among psychosocial variables, depression predicted sexual activity for young women while stress predicted sexual activity for young men. Although there were no gender differences in HIV testing after controlling for demographic and psychosocial variables, there were some differences between young women and young men with regard to predictors of HIV testing. Age and full-time self-employment predicted HIV testing among young women, while part-time self-employment, education, and substance abuse risk predicted HIV testing among young men. Findings suggest a need for gender and youth friendly strategies for addressing the HIV treatment cascade and care continuum.